Terahertz irradiation effects on the morphology and dynamics of actin biopolymer. (23rd June 2021) - Hoshina, Hiromichi; Yamazaki, Shota; Tsubouchi, Masaaki; Harata, Masahiko
Abstract: Our recent experimental research on terahertz (THz) irradiation of actin filaments, which serve as representative biopolymer materials, is summarized in this review. We found that pulsed THz waves with energy density of ∼10 −4 J cm −2 (∼10 8 W cm −2 at the peak) generate acoustic waves efficiently in the aqueous media. These acoustic waves propagated deeply into the water and demolished the actin filaments in living HeLa cells that were submerged into the cell culture medium. The results implied that THz pulsed irradiation affects the biomolecules in the tissues, even if these molecules are located a few millimeters away from the body surface. In contrast, irradiation using THz waves with lower peak power of the order of ∼W cm −2 induces the elongation of the actin biopolymer without thermal or acoustic effects. The polymerization of actin molecules plays essential roles in cell motility, growth, differentiation and gene expression. Therefore, our results indicate that THz waves could be applicable to artificial manipulation of cellular functions.